Development of a Boolean Logic Game for Visual, Auditory and Kinesthetic Learning Styles - Kharisma, Mochammad Mirza; Wardhono, Wibisono Sukmo; Suharsono, Aswin (Department of Informatics Engineering, 2024)
This research aims to develop a top-down game to provide a comfortable learning environment for students with various learning styles. We use the visual, auditory and kinesthetic (VAK) learning style model. Top-down game development meets learning content needs within a Personalized Learning Environment (PLE). PLE is a system that is able to adapt students' characteristics in learning so that they can learn optimally. In this case, we chose Boolean algebra material presented to students taking Discrete Mathematics and Computer Architecture courses. The development of this learning environment uses the 4D method from Thiagarajan up to the third stage (Define, Design, Develop). The Define stage produces an instructional design consisting of Boolean algebra symbol material, Boolean algebra operations, and logic gate operations. The Design stage produces nine mini game designs representing three materials and each available for three learning styles. The nine game designs have been declared in accordance with the objectives of instructional design based on material expert validation. The Develop stage produces a digital game, media experts state that the game meets the parameters of digital game validity.